Full-bore crank-angle resolved imaging of combustion in a four-stroke gasoline direct injection engine - Ma, H; Marshall, S; Stevens, R; Stone, R (2007)
The conventional Bowditch piston arrangement in an optical access engine limits the field of view to about half the bore area. By using a transparent crown (with a flat top) and incorporating a concave surface into the underside of the piston, then the piston crown acts as a diverging lens. Appropriate choice of the radius of curvature and the piston crown thickness provides an image of the full bore. There is of course optical distortion in the image but, since the piston position is known for each image, then it is comparatively simple to reconstruct undistorted images and videos. As an illustration of the technique, results are presented here for flame front tracking, and estimates of the combustion temperature and soot loading by a colour ratio pyrometry technique. This full-bore imaging technique is also applicable to many other optical diagnostic techniques. For a motored engine with particle imaging velocimetry and an optical cylinder liner, then the light sheet could enter either through the piston to illuminate a vertical plane or through the cylinder liner and be imaged through the piston. The choice of laser-based combustion diagnostic techniques would be limited by the transmission range of the piston window. © IMechE 2007.